Superconducting Thick-Films From a Y-Ba-Cu-O Precursor. (1991) - Sacchi, Maurizio; Sirotti, Fausto; Morten, Bruno; Prudenziati, Maria
Abstract : We have prepared screen-printed films of the Y-Ba-Cu-O compound starting from a spray-pyrolysis precursor powder. BeO ceramic substrates are confirmed to be inert with respect to the film up to about 1000 º C. Electrical properties of oxygen annealed films are investigated, evidencing excellent superconducting behaviour, both in terms ofT c ( ≃ 91 K ) and Jc (>10 2 A.cm -2 at 77 K).